The analgesic properties of Yu-Xue-Bi tablets in the inflammatory pain mice: By the inhibition of CCL3-mediated macrophage transmigration into the spinal cord. (10th May 2022) - Zhang, Guoxin; Tian, Congmin; Liang, Tingjun; Chi, Hongyu; Wu, Anguo; Li, Jiahao; Yao, Xuemin; Wang, Qi; Zhu, Chunyan; Lin, Na
Abstract: Ethnopharmacological relevance: Until now, inflammatory pain, especially ones with central sensitization in the spinal cord, is far from effectively treated. Yu-Xue-Bi Tablets (YXB) is a patented medicine, which has been widely applied for inflammatory pain. However, its therapeutic characteristics and mechanism remain unknown. Aim of the study: This study is designed to evaluate the analgesic characteristics and explore the underlying mechanism of YXB in the inflammatory pain model induced by Complete Freund's Adjuvant (CFA). Materials and methods: The analgesic effects were measured by Von Frey test. The expression of calcitonin gene-related peptide (CGRP) was quantified by immunofluorescence. The expression of immune factors was analyzed via Luminex assay. The further quantifications of C–C Motif chemokine ligand 3 (CCL3) were verified by Enzyme-linked immunosorbent assay (ELISA). The transmigration of macrophage and activation of microglia were evaluated by immunofluorescence. Spinal injections of purified CCL3, CCR1 antagonist (J113863) and CCR5 antagonist (Maraviroc) were used to clarify roles of CCL3 assumed in the pharmacological mechanism of YXB. Results: In CFA mice, YXB ameliorated the mechanical allodynia in dose and time dependent way, suppressed the central sensitization in dose dependent way. In the L5 spinal cord, YXB downregulated the expression of macrophage M1 pro-inflammatory factors TNFRI and CCL3, inhibited the transmigration of circulating macrophage and the activation of microglia. Purified CCL3 led to the transmigration of macrophage, activation of microglia, central sensitization, and mechanical allodynia in the Sham mice. Inhibitors of CCR1 and CCR5 attenuated above symptoms in CFA mice. Purified CCL3 blocked YXB mediated down regulation of CCL3, inhibition of macrophage transmigration, but not activation of microglia. Conclusion: YXB exerts the analgesic effects by inhibiting CCL3-mediated peripheral macrophage transmigrate into spinal cord. This study provided a novel approach for inflammatory pain treatment and new insight into the pharmacological action of YXB. Graphical abstract: Image 1